Estimation of immune cell content in tumour tissue using single-cell RNA-seq data - Max Schelker (Nature Portfolio, 2017)
Mathematical approaches can be used to assess immune cell composition from the tumour's bulk expression data. Here the authors optimise the CYBERSORT-based deconvolution algorithm by including cell type-specific reference gene expression profiles generated from tumour-derived single-cell RNA sequencing data.